Case Report: Management of a Multidrug-Resistant CMV-Strain in a Renal Transplant Recipient by High-Dose CMV-Specific Immunoglobulins, Modulation in Immunosuppression, and Induction of CMV-Specific Cellular Immunity - Wiening, Vanessa; Schmidt, Tina; Dahmen, Maximilian; Siam, Sami; Reuter, Stefan; Pavenstädt, Hermann-Joseph; Sester, Martina; Suwelack, Barbara (Frontiers in Immunology, 2021)
The management of multidrug-resistant strains of cytomegalovirus after solid organ transplantation is challenging. This case report demonstrates the successful treatment of a multidrug-resistant strain of cytomegalovirus that may represent a valuable option for problematic cases. This report illustrates the emergence of a multidrug-resistant cytomegalovirus (CMV) UL54 mutant strain in a renal transplant recipient with severe lymphopenia and thrombocytopenia. We show that the combined treatment with high-dose intravenous cytomegalovirus-specific immunoglobulins after the switch to a mammalian target of rapamycin (mTOR)-inhibitor and cyclosporine A was a successful treatment alternative to direct antiviral treatment with high-dose ganciclovir and foscarnet. This treatment was associated with a quantitative induction of CMV-specific CD4 and CD8 T cells that showed maturation in phenotype and functionality with decreasing viral load. Our case report illustrates that high-dose IVIG and conversion of immunosuppressive drugs to mTOR inhibitors and cyclosporine A can be a successful treatment in a situation where the use of direct antiviral drugs was considered insufficient.